Penggunaan Media Film Untuk Meningkatkan Kemampuan Menyimak Siswa Pada Mata Pelajaran Bahasa Indonesia Kelas XI SMA Negeri 7 Wajo - Waode Fitriyan Suri; Umar Mansyur; Andi Puspitasari (Journal on Education, 2023)
This research aims to analyse the process of using film media on students listening abilities and to describe the results of improving students listening abilities. The research method used is Classroom Action Research (PTK). The subjects of this research were 35 students of class XI MIPA 2 SMAN 7 Wajo. The design in this research is that there are four stages, namely planning, implementing actions, observing and reflecting. The data analysis technique used in the research is qualitative descriptive analysis and the results are analysed quantitatively. This research was carried out in 2 cycles, the results of the cycle I of research were 5 students who achieved completeness with a percentage of 14.2%, students who hed not yet achieved completenesss totalled 30 students with a percentage of 85.7%. while in cycle II there were 26 students who achieved completeness with a percentage of 74.6% and there were 9 students who had not achieved completeness with a percentage of 25.1%. The findings in this research are that the use of film media can improve students listening skills in class XI Indonesia Languange SMA Negeri 7 Wajo. Its was concluded that the listening skills using film media for class XI MIPA 2 SMA Negeri 7 Wajo were declared successful.